Nyai Ontosoroh: a Female Hero and Her Resistance to Gender Injustice - Budi Waluyo; Andrik Purwasito; Warto Warto; Slamet Subiyantoro (Faculty of Humanities, Universitas Jenderal Soedirman, 2021)
Nyai Ontosoroh is a character in Pramudya Ananta Toer's novel Bumi Manusia, which depicts a woman's struggle against injustice in her life. R. Giryadi adapted Nyai Ontosoroh's struggle in this novel into a short drama titled